IMPLEMENTATION OF BLENDED LEARNING DESIGN FOR OPERATIONAL MANAGEMENT COURSES (COLLABORATION BETWEEN FACE TO FACE, WEB, YOUTUBE AND TELEGRAM APPLICATIONS) - Robi Awaluddin (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
The challenges and educational opportunities in the era of the industrial revolution 4.0 currently include changes in the way of learning, thinking and acting for students in developing creative innovations in various fields, especially in the field of management science. So with this, students can improve the quality of learning, learning achievement and the ability to understand the abstraction of challenges in the industrial and business world today which is full of speed, innovation and uncertainty in the era of disruption that necessitates change in thinking patterns and learning patterns that are more comprehensive in accordance with technological development. Blended learning is an integrative learning model that can improve student motivation and learning achievement hypothetically in this study. The study was conducted for 4 months with qualitative analysis tools with a population of management study program students using the control class and the class given treatment. The right strategy formulation will be obtained after the hypothesis is answered through this research. In making this system, it is planned to make a lecture using the blended learning method. Where will combine online and conventional learning. The features contained therein allow for the addition of new activities in accordance with the lecture system in general. In this design, there are lectures through YouTube videos, telegram apps, web-based, and face to face / face to face as conventional learning. For videos using YouTube. In the web-based learning contains lecture materials that can be accessed by students on the Moodle page. Lecturers can directly check the results of examinations and student assignments and can directly give grades. This research resulted in 61 percent of students strongly agreeing with the implementation of blended learning, 21 agreeing and 8 quite agreeing with the implementation of blended learning based on youtube, web and telegram apps.